MORPHOMETRIC PARAMETERS OF THE THYMUS GLAND IN THE EARLY ANTENATAL PERIOD OF DEVELOPMENT - Korjavov S.O.; Alkov R.A.; Lutfullayev X.Z.; Ruzikulov X.K.; Yakubova Kh.K. (World Scientific Research Journal, 2025)
Abstract: In the study of materials thymus of embryos and fetuses in the seventh week there were found out the formation of the epithelial bud. 8-9 week showed the population of epithelial cords lymphocytes. By 11-12 weeks of development there were determined by prostate lobes with all their characteristic components. In terms of 18-20 and 27-28 weeks of embryogenesis, the peaks were set to increase the number of thymic cells, was likely to result in an increase of cortical cancer due to proliferation of lymphoblasts subcapsular zone.